Tall, dark and texan eaudiobook Whispering mountains series, book 3. - Thomas, Jodi (Whispering Mountain, 2010)
Listeners flock to USA Today and New York Times best-selling author Jodi Thomas' Texas romances. Teagen McMurray is a rugged cowboy not looking for love. But when Jessie Barton and her three daughters arrive on the scene seeking protection, Teagen discovers he has a heart with room enough for four. "[Thomas'] emotionally moving stories are the kind you want to go on forever."-Romantic Times